Strategy to Improve the Quality of Health Human Resources in Supporting the Effectiveness of Elderly Health Programs at the North Sumatra Provincial Health Office - Aditiawansyah, Muhammad Danu; Junita, Audia; Batubara, Beby Masitho (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to analyze strategies to improve the quality of health human resources (HR) in supporting the effectiveness of elderly health programs at the North Sumatra Provincial Health Office. The primary focus of the research is to evaluate the planning, organization, implementation, and control strategies implemented, as well as identify the factors that hinder the smooth running of the program. This study uses a qualitative descriptive method with the approach of Gary Dessler's HR management theory. The study results show that health human resource planning is focused on the availability of health workers in terms of the number and qualifications needed. This process involves performance evaluation, work plan preparation, and cross-sector coordination. Organizing is carried out in stages, starting from the Provincial Health Office, Regency/City Health Office, to Puskesmas and Posyandu for older people. In its implementation, the Health Office coordinates with various parties to ensure the involvement of key and supporting health workers in the Ministry of Health's policies. Effective leadership from the Head of Public Health plays a vital role in monitoring and evaluating programs through coaching and direction, and motivating health workers to improve performance and resolve emerging obstacles. However, this study found several obstacles, including a lack of coordination across programs, delayed response of human resources to information updates, and suboptimal communication.